Contact-independent exposure to Rhodococcus rhodochrous DAP96253 volatiles does not improve the survival rate of Myotis lucifugus (little brown bats) affected by White-nose Syndrome - Sarah Hooper; Sybill Amelon (PeerJ, 2023)
Since the emergence of White-nose Syndrome, a fungal disease in bats, caused by Pseudogymnoascus destructans, hibernating populations of little brown bats (Myotis lucifugus) have declined by 70–90% within P. destructans positive hibernacula. To reduce the impact of White-nose Syndrome to North American little brown bat populations we evaluated if exposure to volatile organic compounds produced by induced cells from Rhodococcus rhodochrous strain DAP96253 could improve the overwinter survival of bats infected by P. destructans. Two simultaneous field treatment trials were conducted at natural hibernacula located in Rockcastle and Breckinridge counties, Kentucky, USA. A combined total of 120 little brown bats were randomly divided into control groups (n = 60) which were not exposed to volatile organic compounds and treatment groups (n = 60) which were exposed to volatile organic compounds produced by non-growth, fermented cell paste composed of R. rhodochrous strain DAP96253 cells. Cox proportional hazard models revealed a significant decreased survival at the Rockcastle field trial site but not the Breckinridge field site. At the Breckinridge hibernacula, overwinter survival for both treatment and control groups were 60%. At the Rockcastle hibernacula, Kaplan-Meier survival curves indicated significantly increased overwinter survival of bats in the control group (43% survived) compared to the treatment group (20% survived). Although complete inhibition of P. destructans by volatile organic compounds produced by induced R. rhodochrous strain DAP96253 cells was observed in vitro studies, our results suggest that these volatile organic compounds do not inhibit P. destructans in situ and may promote P. destructans growth.